Young people's online communication and its association with mental well‐being: results from the 2019 student health and well‐being survey. Issue 1 (16th November 2022) - Anthony, Rebecca; Young, Honor; Hewitt, Gillian; Sloan, Luke; Moore, Graham; Murphy, Simon; Cook, Steven
Abstract : Background: Online communication has become an integral aspect of daily life for young people internationally. Very little research has examined whether the association between social media use and well‐being depends on who young people engage with (i.e. real, or virtual friendships). Methods: Data were drawn from a subsample of students ( N  = 38, 736) who took part in the School Health Research Network (SHRN) 2019 Student Health and Well‐being (SHW) survey. A series of multivariable regression models were used to assess the association between who adolescents were communicating with online and well‐being, controlling for confounders: passive social media use; friendship quality; and cyberbullying. We also tested whether these associations were modified based on gender. Results: Students are highly engaged on social networking sites, and these sites are used to communicate with existing friendship groups and develop virtual friendships. Frequent online communication with best friends ( b  = .340, p  < .001) and bigger friendship groups ( b  = .397; p  < .001) was associated with higher levels of well‐being. However, the frequency of online contact with virtual friends made online was negatively and significantly associated with well‐being ( b  = −.760; p  < .001), with a larger negative association for girls than boys. Conclusions: Online communication with virtual friendship networks were associated with lower mental well‐being, with stronger associations for girls than boys; however, frequent online communication with 'real' friends was associated with better well‐being. Our results indicate the importance of considering the nature of adolescent online communication, rather than just its quantity, in developing interventions to improve adolescent well‐being.